Disregard and danger: Chimamanda Ngozi Adichie and the voices of trans (and cis) African feminists. Issue 4 (July 2020) - Camminga, B
In March of 2017, best-selling Nigerian author and feminist Chimamanda Ngozi Adichie, in an interview with Britain's Channel 4, was asked whether being a trans woman makes one any less of a 'real woman?' In the clip, which went viral shortly thereafter, Adichie responded by saying 'When people talk about, "Are trans women women?" my feeling is trans women are trans women.' Echoing the essentialist, predominantly white Global Northern, feminist politics of trans-exclusionary feminists (TERFs), by implying that trans women are not 'real' women because, as she assumes, they benefited from male privilege, Adichie set off a social media maelstrom. The publicised responses to her comments largely came from feminists and trans women in the Global North, and though many trans people from the African continent responded, with hashtags such as #ChimamandaKilledME, very few of these received any attention. As the hashtag suggests, for trans people living on the African continent, given the general lack of recourse to rights, Adichie's words as an African writer carry considerable weight. Given this, the absence of media attention is curious. This article offers a recentring, by focusing on those voices, maligned in the broader debate – trans people from the African continent. I argue that while Adichie might be stumbling over the questions that lie at the heart of TERF politics (what does it mean to be a woman? and does it matter how a person arrives at being a woman?), trans women on the African continent have been busy reconstituting the terms of the terrain.